Comparison of the biomechanical differences in the occlusal movement of wild-type and BMP9 knockout mice with apical periodontitis - Peng, Mengtian; Ma, Xiaofei; Cao, Yuying; Wang, Chunjuan; Tan, Qin; Chu, Xinyue; Zhou, Pengfei; Fu, Tiwei; Liang, Panpan; Ran, Shidian; He, Tong-Chuan; Wang, Jinhua; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Apical periodontitis is a common clinical disease caused by bacteria; bacterial metabolites can cause an imbalance in bone homeostasis, bone mass reduction, and tooth loss. Bone resorption in apical periodontitis causes a concentration of stress in the tooth and periodontal tissues during occlusion, which aggravates the disease. Emerging evidence indicates that bone morphogenetic protein 9 (BMP9), also known as growth differentiation factor 2(Gdf2), may play an important role in tooth and alveolar development. Here, we investigated the role of BMP9 in the development of apical periodontitis and its effects on dentoalveolar bone biomechanics. Apical periodontitis models were established in a total of five BMP9 knockout (KO) mice and five C57BL/6 WT (wild-type) mice. At baseline and 14, 28, and 42 days after modeling, in vivo micro-computed tomography analysis and three-dimensional (3D) reconstruction were performed to evaluate the range of the apical lesion in each mouse, confirm that the animal model was successfully established, and determine the stress mode of the partial structure. Finite element analysis (FEA) was performed to study the stress and strain at the alveolar fossa of each mouse under the same vertical and lateral stress. FEA revealed that the stress and strain at the alveolar fossa of each mouse gradually concentrated on the tooth cervix. The stress and strain at the tooth cervix gradually increased with time but were decreased at day 42. Under the same lingual load, the stress and strain at the root of the tooth in KO mice were greater than those in WT mice. Thus, these findings demonstrate that BMP9 affects the biomechanical response of the alveolar fossa at the root of the tooth in mice with apical periodontitis. Moreover, the effects of BMP9 on the biomechanical response of the dentoalveolar bone may be site-dependent. Overall, this work contributes to an improved understanding of the pathogenesis of apical periodontitis and may inform the development of new treatment strategies for periapical inflammation.